Differential gene regulation in human small airway epithelial cells grown in monoculture versus coculture with human microvascular endothelial cells following multiwalled carbon nanotube exposure - Snyder-Talkington, Brandi N. (Toxicol Rep, 2019)
Concurrent with rising production of carbon-based engineered nanomaterials is a potential increase in respiratory and cardiovascular diseases due to exposure to nanomaterials in the workplace atmosphere. While single-cell models of pulmonary exposure are often used to determine the potential toxicity of nanomaterials in vitro, previous studies have shown that coculture cell models better represent the cellular response and crosstalk that occurs in vivo. This study identified differential gene regulation in human small airway epithelial cells (SAECs) grown either in monoculture or in coculture with human microvascular endothelial cells following exposure of the SAECs to multiwalled carbon nanotubes (MWCNTs). SAEC genes that either changed their regulation direction from upregulated in monoculture to downregulated in coculture (or vice versa) or had a more than a two-fold changed in the same regulation direction were identified. Genes that changed regulation direction were most often involved in the processes of cellular growth and proliferation and cellular immune response and inflammation. Genes that had a more than a two-fold change in regulation in the same direction were most often involved in the inflammatory response. The direction and fold-change of this differential gene regulation suggests that toxicity testing in monoculture may exaggerate cellular responses to MWCNTs, and coculture of cells may provide a more in-depth assessment of toxicological responses.